(untitled) (Journal of the Bangladesh Agricultural University, 2014)
There is no reliable information till now on the conversion rate of agricultural land in Bangladesh into different non agricultural sectors. The study was undertaken to estimate the present land use pattern and to calculate the changes in land use of agricultural and non-agricultural field over time using aerial photographs of Trishal and Fulbaria upazila of Mymensingh district. Two series of aerial photographs of both upazilas from 1983 and 2000 at scales of 1:40,000 and 1:25,000, respectively, were studied. Land use categories were calculated by random line drawing method on effective areas of aerial photograph. In 1983, Total agricultural and non-agricultural land of Trishal upazila were found 29,505 and 4,095 ha accounting 87.81 and 12.2% of total land area, respectively. In Fulbaria upazila for the same year, it was 35,611 and 4,258 ha accounting 89.3% and 10.7% of total land area, respectively,. An amount of about 3545 and 3637 ha agricultural land was transformed into non-agricultural land in Trishal and Fulbaria upazila, respectively, within a period of 17 years. The rate of decreasing agricultural land to non agricultural land in Trishal and Fulbaria upazila was estimated to be 0.62 and 0.54% /annum, respectively. Land use analysis shows that conversion of agricultural land into settlement, transport network and water body contributed 88.07, 5.3 and 6.63% of the land loss, respectively in Trishal upazila and 98.45, 1.3 and 0.12% of the land loss, respectively in Fulbaria upazila. If similar trends in loss of agricultural land remain constant, there will be no land available for cultivation after around 200 years. Therefore, it is very crying need for the country to make a land use policy for food security of the rapidly growing population. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21210 J. Bangladesh Agril. Univ. 12(1): 13-18, 2014